O-013 Cerecyte coil trial: the clinical outcome of endovascular coiling in patients with ruptured and unruptured intracranial aneurysms treated with Cerecyte coils compared with bare platinum coils. Results of a prospective randomized trial. (16th November 2010) - Molyneux, A; Coley, S; Sneade, M; Mehta, Z
Abstract : Purpose: To report the discharge and 6 month clinical outcomes in patients treated with Cerecyte or bare platinum coils in a prospective randomized trial. Material and methods: 500 patients were enrolled in the Cerecyte prospective randomized trial, in 23 centers worldwide. 263 patients were treated for a previously unruptured aneurysm and 234 with a recently ruptured aneurysm who were in grade 1 or 2 after subarachnoid hemorrhage (SAH). A secondary outcome of the trial was to collect the clinical outcomes and any differences between the allocated groups. This methodology allowed investigators to examine accurately, in a large multicenter trial, the clinical outcomes associated with treating patients with current expertise and coil technology, and to determine if there are any significant differences between the coil types in respect of clinical complications and outcomes. The clinical outcomes were determined at discharge and after 6 months of follow-up by a validated self-reported modified Rankin Scale (mRS) of dependency. The data were analyzed to examine procedural complications, discharge outcomes, lengths of stay and dependency at 6 months. Results: 497 patients underwent coil treatment of their aneurysm: 234 patients with recently ruptured aneurysms (RA) and 263 with unruptured aneurysms (UIA). Of the 234 patients with RA, discharge data were available for 227 (97%) at the time of abstract preparation. Aneurysm rupture was reported in 14/227 (6%) and thromboembolic complications were reported in 13/227 (6%). Non-procedural complications reported included delayed cerebral ischemia in 30/232 (13%) and hydrocephalus requiring intervention in 7/232 (3%). 220/227 (97%) patients were WFNS grade 1 or 2 at discharge, two were in poor grade (WFNS 3 and 4) in hospital and death occurred in 2/231 (1%) patients. At the 6 month follow-up, 210/218 patients were independent (mRS 0–2) (96%), four were dead (2%) and four were dependent (mRS 3 or 4). In 263 patients with UIAs, procedural aneurysm rupture occurred in six (2%) and thromboembolic events occurred in 15 (3.8%). There was non-procedural neurological deterioration in 7/259 (3%). Hydrocephalus was reported in one patient who had sustained a procedural subarachnoid hemorrhage. There were no inhospital deaths and 255/259 (98%) patients were discharged home. At discharge, 247/253 patients with data were mRS 0 or 1 and six were mRS 2. At the 6 month follow-up, thromboembolic complications were reported in 4/231 (2%), headache in 17/231 (7%) and neurological deterioration in 4/231 (2%). There were no reports of hydrocephalus. Clinical outcome data were available for 229 patients at the 6 month follow-up. 224/229 were mRS 0–2 (95%): score 0 or 1=213 and score 2=11. One patient had died, one was mRS 4 and three were mRS 3. No delayed haemorrhages were reported. The clinical outcomes by coil type will be reported. Conclusion: The study will provide comparative safety data of the two coils types and the overall safety of coiling in patients treated for unruptured cerebral aneurysms, and those in good grade after SAH.